2019
DOI: 10.1186/s12935-019-1040-6
|View full text |Cite
|
Sign up to set email alerts
|

Silencing expression of PHF14 in glioblastoma promotes apoptosis, mitigates proliferation and invasiveness via Wnt signal pathway

Abstract: BackgroundThe plant homeodomain (PHD) finger protein 14 (PHF14) is a vital member of PHD finger protein families. Abnormal expression of PHF14 has been identified in various cancers and is known to be implicated in the pathogenesis of tumors. This study investigates the role and the underlying mechanisms of PHF14 in GBM (glioblastoma multiforme).MethodsTissue microarrays and public databases interrogation were used to explore the relationship between the expression of PHF14 and GBM. Three stable PHF14-silenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…We show here that HMG20A and PHF14 share an important number of targets related to the mesenchymal phenotype of the TNBC cell line MDA-MB-231. Defects in migration and invasion due to PHF14 KD have been previously reported in glioblastoma multiforme, lung, bladder and gastric cancer cell lines ( 44 , 45 , 82 , 83 ). However, the signaling pathways involved in this regulation are unclear.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…We show here that HMG20A and PHF14 share an important number of targets related to the mesenchymal phenotype of the TNBC cell line MDA-MB-231. Defects in migration and invasion due to PHF14 KD have been previously reported in glioblastoma multiforme, lung, bladder and gastric cancer cell lines ( 44 , 45 , 82 , 83 ). However, the signaling pathways involved in this regulation are unclear.…”
Section: Discussionmentioning
confidence: 68%
“…have proposed that PHF14 modulates the AKT-mTOR pathway ( 44 , 45 ), while Wu et al. reported that the Wnt signaling pathway is affected by PHF14 silencing ( 83 ). However, our results in MDA-MB-231 cells revealed that the AKT-mTOR signaling pathway was not affected by either HMG20A or PHF14 KD, and our RNA-seq transcriptomic analysis does not support the downregulation of Wnt signaling in either KD condition.…”
Section: Discussionmentioning
confidence: 99%
“…Some study illustrates that PHD finger proteins generally promote proliferation and migration in cancer cells [25,37], which is also consistent with our results. A latest study indicates that silencing PHF14 induces apoptosis in glioblastoma cells [39]; however, there is no apoptosis in gastric cancer cells after knocking down of PHF14, which remind us that PHF14 plays different roles in different cancers. e different role of PHF14 may be induced by activation of different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This is a profound platform that can be utilized to analyze the current and future trends in the diagnosis and prognosis of glioma from molecular biology to proteomics. Recent studies disclosed several signal pathways that closely related to the proliferation and metastasis of glioma, such as IGF-1R/AKT, Notch, mTOR, Wnt and EMT (28)(29)(30)(31)(32). EMT is an indispensable part of the normal development process of the human body, and it also plays a crucial role in tumor progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%